Mathematical Simulation of Metamaterial Solar Cells (Advances in Applied Mathematics and Mechanics, 2021)
In this paper, we propose several solar celldesigns based on metamaterials. Extensive numerical simulations of variousdesigns with different materials are carried out.Our tests show that metamaterial solar cells are quite efficient, andover 80% and 90% absorption rates can be attained for solar spectrum andvisible rays, respectively.